CRISPR/Cas9 library screening for drug target discovery. Issue 2 (February 2018) - Kurata, Morito; Yamamoto, Kouhei; Moriarity, Branden; Kitagawa, Masanobu; Largaespada, David
Abstract CRISPR/Cas9-based tools have rapidly developed in recent years. These include CRISPR-based gene activation (CRISPRa) or inhibition (CRISPRi), for which there are libraries. CRISPR libraries for loss of function have been widely used to identify new biological mechanisms, such as drug resistance and cell survival signals. CRISPRa is highly useful in screening for gain of functions, and CRISPRi is a more powerful tool than RNA interference (RNAi) libraries in screening for loss of functions. Positive selection using a CRISPR library can detect survival cells with specific conditions, such as drug treatment, and it can easily clarify drug resistance mechanisms. Negative selection is capable of detecting dead or slow-growing cells efficiently, and it can identify survival-essential genes, which can be promising candidates for molecularly targeted drugs. In addition, negative selection can be applied for synthetic lethality interactions, where the perturbation of both genes simultaneously results in the loss of viability, but that of either gene alone does not affect viability. This mechanism is highly important to identifying the optimal combination of molecularly targeted drugs. Survival-co-essential genes in cancer cells can be identified using new methods, such as the paired guide RNA system and in combination with single-cell RNA sequencing techniques. These efficient methods can clarify interesting biological mechanisms and suggest candidates for molecularly targeted drugs. This review identifies what types of screenings were performed and suggests ideas for the next CRISPR screenings to develop new drugs.